Laboratory Investigations Of Susceptibility, Infectivity, And Transmission Of Perkinsus Marinus In Oysters - Chu, Fu-Lin C. (W&M ScholarWorks, 1996)
The protozoan parasite, Perkinsus marinus (Dermo), has caused significant mortality in the eastern oyster, Crassostrea virginica, along the east coast of the United States and the Gulf of Mexico, since the 1950s. Because of its current expanded distribution and increased abundance, P. marinus is now considered more prevalent in the mid-Atlantic waters and the Chesapeake Bay in particular, than another protozoan pathogen, Haplosporidium nelsoni (MSX). The susceptibility, infectivity/pathogenicity, and transmission of P. marinus in eastern oysters were investigated in numerous laboratory studies, The influence of environmental factors such as temperature, salinity, and pollution on the interaction between the host oyster and the parasite were also examined. Three P. marinus life stages, the meront, prezoosporangia, and biflagellated zoospore, were found effective in transmitting the disease. The meront stage was more effective than the prezoosporangia stage in transmitting the disease in eastern oysters, suggesting that the meront is the primary transmission agent in nature. A dose of 10-10(2) freshly isolated P. marinus cells oyster(-1) was required to cause infection by direct shell cavity injection. P. marinus susceptibility and disease progression were positively correlated with temperature, salinity, and number of infective cells the oyster encountered. Temperature appeared to be the most important factor, followed by the infective cell dose, and then salinity in determining the subsequent disease development in oysters. There was no significant interaction between temperature, salinity, and infective cell dose on the prevalence of disease in oysters. However, the interaction between either temperature and salinity or between temperature and P. marinus dose significantly intensified the disease. The Pacific oyster, Crassostrea gigas, was less susceptible, but not completely resistant, to P. marinus compared to the eastern oyster, C. virginica. However, the Pacific oyster was intolerant of high temperature ...